Morphological and functional analysis of the loading regimen with intravitreal ranibizumab in neovascular age-related macular degeneration. Issue 2 (18th August 2009) - Bolz, M; Simader, C; Ritter, M; Ahlers, C; Benesch, T; Prünte, C; Schmidt-Erfurth, U
Abstract : Aim: To quantify and correlate the morphological and functional effects of the recommended loading regimen with intravitreal ranibizumab in neovascular age-related macular degeneration (AMD). Methods: In a prospective, interventional clinical trial, 29 consecutive patients (29 eyes) with choroidal neovascularisation secondary to AMD received three initial monthly intravitreal injections of ranibizumab. During this loading regimen, best corrected visual acuity (BCVA) and microperimetry (MP) testing, as well as optical coherence tomography and fluorescein angiography (FA), were performed using a standardised protocol and the results correlated. Results: Significant morphological and functional therapeutic effects were observed as early as 1 week following the first treatment. Throughout the loading-dose period, central retinal thickness, including intraretinal cysts and subretinal fluid, decreased fast and significantly (p<0.01); pigment epithelial detachment resolved less rapidly. The mean leakage area by FA decreased (p<0.01) and retinal function (BCVA and MP) increased significantly (both p<0.01). However, the change in morphology and function was only significant between baseline and week 1. There was no significant additional morphological or functional benefit following the second and third injection. Conclusion: The initial administration of intravitreal ranibizumab in neovascular AMD induced a significant effect on intra- and subretinal fluid and visual function; subsequent injections had a less pronounced effect. It remains to be determined whether this loading regimen should be mandatory in all patients or if a single dose regimen would lead to a comparable functional and morphological retinal improvement.